Beach Nourishment: A 21st Century Review (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Erosion is experienced by most coastlines worldwide, and it is usually attributed not only to sea level rise but also to the retention of sand in dams, the occupation of dry beaches by urbanized areas, the mining of sand as a building material for construction, and so on. Beach nourishment has evolved as the favored erosion-mitigation strategy in many areas of the world. The increasing number of people living on the coast, the safety of those people, and the high values of coastal properties are all factors that have made beach nourishment a cost-effective strategy for managing erosion in many locations. However, a new scenario of sand scarcity and environmental care has arisen in recent decades. There have been many different and interesting cases of various aspects of beach nourishment in recent years. The purpose of this invited Special Issue is to publish the most exciting experience and research with respect to this topic. Thus, novel techniques for designing, executing, and controlling these kinds of works as well as different case studies and their monitoring results and conclusions have been included, in order to present an updated state of the art for marine scientists, researchers, and engineers.